Association between the pattern of play and the outcome of matches during the 2015 Asian Football Confederation (AFC) according to ball possession - Zhu, H. Z.; Mohd, A. A.; Muhamad, N. M.; Muhamad, S. S. A. (Journal of Physical Education and Sport, 2022)
The pattern of play is a frequently used term by coaches, sports scientists, performance analysts and the media to refer to the sports style of teams within a game. For invasion games, the game plan and strategy are crucial factors that affect the results of a match, making it essential to calculate the strategic dimensions of the game. The use of measurable methods in sports science allows one to analyse and clarify the complexities of a match. Recent studies have examined ball possession and its relation between patterns of play with the outcome of a match. This is often determined by the location of the match, the nature of the opponent and the line score since teams can use different patterns of play when ahead, level or behind. There are several reasons why one team would win a match while the other loses. Previous research found that teams who frequently possess the ball during a match will have plenty of opportunities to score goals and win the game, while the other team with fewer opportunities will lose the game. A correlational design study is conducted to determine the relationship between playing styles and the outcome of matches. A total of 42 teams (N=42) from the 2015 Asian Football Confederation have been chosen. Notational analysis is used to further understand the relevant properties. The outcomes reveal that out of 42 teams, 17 winning teams (73.9%) and 6 losing teams (26.0%) implemented an attacking pattern of play, while 4 winning teams (21.0%) and 15 losing teams used a defensive pattern of play (78.9%). The chi-square test of independence is used to determine the association between the playing styles of teams and the outcomes of matches: X2 (1, n = 42) = 0.524, p = 0.001, phi = 0.001. The independent t-test reveals no significant difference between ball possession for winning (M = 49.62, SD = 5.844) or losing (M = 49.43, SD = 5.887); t (40) = 0.105, p = 0.917. It can be concluded that although there is a significant association between the playing pattern and the outcome of a match, the ball possession for both outcomes is similar.